A IMPLEMENTASI SERVICE EXCELLENCE OLEH CUSTOMER SERVICE PADA BMT BISMILLAH SUKOREJO - Alif Arfian Syah Alif (Institut Agama Islam Negeri Parepare, 2020)
As a well-known microfinance institution in Sukorejo, BMT Bismillah wants to always maintain its existence, by always providing service excellence to its customers so that customers become satisfied and loyal. For service excellence to be carried out, surely there must be a subject or actor who can deliver excellent service which is the main goal. The subject or actor intended is a customer service. BMT Bismillah certainly has service excellence standards that must be applied by customer service. Therefore, the authors are interested in researching how the service excellence implemented by Bismillah Sukorejo BMT customer service by analyzing it using existing standards. The main problem in this study is how the implementation of service excellence standards for services that actually occur in BMT Bismillah carried out by customer service. This type of research is field research by taking the location of research in BMT Bismillah Sukorejo using a qualitative approach. The data in this study consisted of primary data and secondary data obtained using the method of interviews (interviews) with customer service, documentation and observation. The results showed that customer service is able to implement the standards set by BMT Bismillah into services that have become its work, but not just any service but excellent service (service excellence) which includes the basic aspects ofAccountability, Action, Attention, Appearance, Attitude, Ability that is able to satisfy and attract customers to remain loyal to BMT Bismillah.Keyword : Service Excellence, Customer service, BMT Bismillah BMT Bismillah Prime ServicStandards